Systematic review of the impact of demographic and socioeconomic factors on quality of life in ostomized colorectal cancer survivors. (4th May 2019) - Kristensen, Helle Ø; Thyø, Anne; Christensen, Peter
Abstract: Background: Formation of a fecal stoma may be necessary to ensure radical resection in colorectal cancer (CRC) patients but will substantially impact the health-related quality of life (HRQoL) in about 20% of cases. Little is known about patient-related risk factors for reduced HRQoL in patients with a permanent stoma. We, therefore, reviewed the current literature on how demographic and socioeconomic factors affect HRQoL in CRC survivors with a stoma. Material and methods: The databases Pubmed, Embase, CINAHL, and PsycINFO were systematically searched. Two independent reviewers extracted and quality-assessed eligible publications. Studies assessing HRQoL using a validated questionnaire at least 6 months after surgery for CRC were included if data on the impact of demographic and/or socioeconomic, factors on HRQoL were analyzed and presented. Results: Eligible studies predominantly presented small cross-sectional cohorts. Age showed equivocal results; hence, some studies found younger patients had inferior HRQoL compared with older patients, and others found no difference. Subdivision into age groups differed widely. Several studies found that both generic and stoma-specific HRQoL was lower in females compared with males. Most studies found that socioeconomic factors did not affect HRQoL while one study found lower education correlated to reduced HRQoL. Categorization of these factors also varied widely. Conclusions: This is to our knowledge the first systematic review on the impact of patient-related factors on HRQoL in long-term CRC survivors. We found that a stoma had more impact in younger ostomates than older and that HRQoL in females was reduced more than in males. Conclusions regarding other factors were difficult due to few studies and contradictory results. Further research in this subject is much needed in order to target preventive measures when planning surgery in patients in high risk of reduced HRQoL.